2020
DOI: 10.3390/ijms21093039
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Developing Biomarker-Based Major Depressive Disorder Diagnostics

Abstract: The identification of biomarkers associated with major depressive disorder (MDD) holds great promise to develop an objective laboratory test. However, current biomarkers lack discriminative power due to the complex biological background, and not much is known about the influence of potential modifiers such as gender. We first performed a cross-sectional study on the discriminative power of biomarkers for MDD by investigating gender differences in biomarker levels. Out of 28 biomarkers, 21 biomarkers were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
(50 reference statements)
2
10
0
Order By: Relevance
“…Jentsch et al reported higher serum and urine resistin levels in MDD patients. Also, they identified these elevations were more in females than males in a recent gender-specific investigation [53]. Also, another study discovered a positive association between resistin levels and atypical depressive symptoms.…”
Section: Plos Onementioning
confidence: 86%
“…Jentsch et al reported higher serum and urine resistin levels in MDD patients. Also, they identified these elevations were more in females than males in a recent gender-specific investigation [53]. Also, another study discovered a positive association between resistin levels and atypical depressive symptoms.…”
Section: Plos Onementioning
confidence: 86%
“…Within the psychiatric biomarker eld, several studies have identi ed potential biomarkers which could be utilized within a diagnostic setting but results varied and the road to actual clinical application is still long [6, 9,12,13,[34][35][36]. The complex underlying biological background of psychiatric disorders may however not be the only explanation for the huge variations in biomarkers studies.…”
Section: Discussionmentioning
confidence: 99%
“…serum/urine was obtained from an existing cohort of 40 patients with MDD, included based on a MINI diagnostic interview, for which biomarker data and HAM-D score were available [12]. Biomarker selection was performed on the basis of our previous work [12,13] and supplemented with Acetyl L-Carnitine as recent literature suggested that this biomarker may be implicated in the pathophysiology of MDD [22].…”
Section: Sample Materials and Biomarker Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, recent focus shifted to nding disease, associated multiple biomarker patterns. Such an approach has shown to be fruitful by recent studies showing promising biomarker panels for major depressive disorder (MDD) (Bilello et al, 2015;Chen et al, 2018;Jentsch et al, 2020;Liu et al, 2015;van Buel et al, 2019). However, as multiple biomarkers are needed to identify a disorder, the margin of error in terms of reliability is considered small, demanding a high application stringency which currently hampers the advancement of these panels from a research setting to a clinical stage (Drucker and Krapfenbauer, 2013;Mcdermott et al, 2013).…”
Section: Introductionmentioning
confidence: 99%